2017
DOI: 10.1186/s12947-017-0101-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of food intake on myocardial performance index

Abstract: BackgroundMyocardial performance index (MPI) has been investigated in a variety of populations, but the effect of food intake has not been evaluated. We assessed whether myocardial performance index is affected by food intake in healthy subjects.MethodsTwenty-three healthy subjects aged 25.6 ± 4.5 years were investigated. MPI was measured before, 30 min after, and 110 min after a standardized meal.ResultsMPI decreased significantly (P < 0.05) from fasting values 30 min after the meal, and had almost returned t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…[13][14][15] Indeed, researchers have previously used DTI-obtained right ventricular parameters to detect early lesions in diabetic patients. 16 This study showed that DTI can accurately reflect RV systolic and diastolic function along the long axis and provide a basis for diagnosing CSFP patients. Specifically, when E/A is less than one, right ventricular diastolic function is normal.…”
Section: Discussionmentioning
confidence: 72%
“…[13][14][15] Indeed, researchers have previously used DTI-obtained right ventricular parameters to detect early lesions in diabetic patients. 16 This study showed that DTI can accurately reflect RV systolic and diastolic function along the long axis and provide a basis for diagnosing CSFP patients. Specifically, when E/A is less than one, right ventricular diastolic function is normal.…”
Section: Discussionmentioning
confidence: 72%
“…[1][2][3][4] Digestion of food is known to alter hemodynamics, [5][6][7] and we have previously shown that both systolic and diastolic functions are affected significantly when comparing echocardiographic exams during fasting and after a meal in a young population. [8][9][10][11] Though the findings might not be of consequence for clinical evaluations in everyday practice, they suggest that the effects of food consumption should be considered, in studies, especially if the sample size is small. [8][9][10][11] The cardiovascular system changes with increasing age, both physiologically and not so rarely pathologically.…”
Section: Introductionmentioning
confidence: 95%
“…[8][9][10][11] Though the findings might not be of consequence for clinical evaluations in everyday practice, they suggest that the effects of food consumption should be considered, in studies, especially if the sample size is small. [8][9][10][11] The cardiovascular system changes with increasing age, both physiologically and not so rarely pathologically. [12][13][14][15][16] Hence, senior people are an important target group in cardiovascular studies.…”
Section: Introductionmentioning
confidence: 95%
“…For instance, we did not have information on food intake, which is known to influence the MPI as obtained by the conventional method. 21 However, the data were collected according to a structured chart as part of the CT protocol, which reduces the bias regarding data collection. We adjusted for the SCORE chart risk factors; however, we did not have biochemical information on cholesterol levels, so we could not adjust for this parameter.…”
Section: M Itati O N Smentioning
confidence: 99%
“…Accordingly, the study is limited by some details not being available. For instance, we did not have information on food intake, which is known to influence the MPI as obtained by the conventional method 21 . However, the data were collected according to a structured chart as part of the CT protocol, which reduces the bias regarding data collection.…”
Section: Limitationsmentioning
confidence: 99%